Double-Blind Randomized Clinical Trial of the Effects of Ezetimibe on Postprandial Hyperlipidaemia and Hyperglycaemia - Inazumi, Koji; Orime, Kazuki; Kawakami, Chihiro; Shirakawa, Jun; Miyazaki, Takashi; Yamakawa, Tadashi; Wakasugi, Tadashi; Watanabe, Shinichiro; Kikuchi, Kaori; Terauchi, Yasuo; Sato, Koichiro; Nezu, Uru; et al. (Journal of Atherosclerosis and Thrombosis, 2012)
Aim: Ezetimibe selectively blocks intestinal cholesterol absorption by inhibiting Niemann-Pick C1-like 1 (NPC1L1) and reducing LDL cholesterol (LDL-C). In animals, ezetimibe reversed diet-induced obesity, liver steatosis, and insulin resistance. In humans, its potential effects on liver steatosis and insulin resistance have been suggested. We investigated the effects of ezetimibe on postprandial hyperlipidaemia and hyperglycaemia in obese subjects with dyslipidaemia in a double-blind randomized crossover trial. Methods: Twenty obese men with hypertriglyceridaemia were assigned randomly to an ezetimibe- or a placebo-precedence-treated group. Subjects in the ezetimibe group were treated with ezetimibe (10 mg/day) for the first 4 weeks, followed by a 4-week interval and then treated with placebo for another 4 weeks. The placebo group received these treatments in reverse order. Subjects were requested to fast for at least 12 hours and then received a standard meal. Blood samples were collected at 0, 30, 60, 120, 240, 360 and 480 minutes after the meal on Days 0, 28, 56 and 84 and were used to measure the lipid and glucose metabolism markers. Results: Ezetimibe significantly decreased the postprandial serum triglyceride excursion (p=0.01) and fasting serum LDL-C, remnant-like particles(RLP) and ApoB48 levels (p<0.05). Postprandial glucose excursion, serum insulin levels, serum glucose-dependent insulinotropic polypeptide (GIP) and active glucagon-like peptide-1 (GLP-1) were not significantly affected by ezetimibe treatment. Conclusion: Ezetimibe restored the postprandial dysregulation of lipid but did not affect glucose metabolism in a double-blind randomized crossover trial.